Wide-ranging performance of different eGFR equations in stage determination of Chronic Kidney Disease patients from endemic areas for CKD in Sri Lanka - Silva, Athige R. N.; Jayasekara, J. M. Kithsiri B.; Nanayakkara, P. G. Chandra L.; Gunawickrama, S. H. Nandana P. (International Journal Of Community Medicine And Public Health, 2023)
Background: Chronic kidney disease of unknown etiology (CKDu) is a public health issue at epidemic proportions in North Central, Uwa and other provinces of Sri Lanka. The initial diagnosis and stage determination of the disease are based on estimated glomerular filtration rate (eGFR), and urine albumin to creatinine ratio (UACR) particularly at community level screening. In this context, harmony and performance of pertaining equations were verified. Methods: Three hundred and ninety-nine (399) volunteer CKD patients were recruited from select CKDu high prevalence areas (Padaviya, Girandurukotte, and Mahiyanganaya). Performance of kidney dysfunction determinants; serum creatinine (SCr), and serum Cystatin C (CysC), as well as markers; UACR, and eGFR variants; SCr based MDRD, SCr based EPI, serum CysC based EPI and SCr and CysC based EPI were scrutinized in terms of kidney disease improving global outcomes (KDIGO) heat-map guidelines. Results: Notable deviation was observed between SCr-based and CysC-based equations at early development of the disease (stage G1) suggesting that the latter may tend to under estimate disease development initially. UACR successfully confirmed diagnosis from eGFR equations including G1 proteinuric subjects (G1). Conclusions: Comparative study of marker performances should improve eGFR based identification of initial CKDu cases in Sri Lanka.